COMPETENCE CHARACTERISTICS OF INDIGENOUS COUNSELOR IN SERAT CENTHINI - Fauziyati Alimah; Ahmad Fauzi (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
In a counseling process, both counselors and counselees each bring personal characteristics including cultural background. The cultural approach in guidance and counseling is very suitable for a plural cultural environment, such as Indonesia. However, counseling science in Indonesia is still dominated by theories from the West. However, counselors cannot blindly apply counseling knowledge developed by different cultural standards. This is because research results in different cultural contexts are not necessarily compatible with Indonesian culture. Therefore, this research aims to help enrich the science of typical Indonesian counseling, namely exploring concepts related to the competency characteristics of indigenous counselors based on local Indonesian wisdom in the context of Javanese culture, which is contained in Serat Centhini. This research is library research. Meanwhile, data analysis in this research uses content analysis techniques with analysis units at the sentence level. This research uses an Indigenous Counseling approach and is pioneering research in the development of the Indigenous Counseling concept. The research results show that the concept of quality characteristics of indigenous counselors in Serat Centhini includes cultural competence and mainstream/general competence. Several aspects found in cultural competence are the awareness aspect which is shown by the value of unconditional acceptance of all cultural things brought by the counselee and treating them well and sincerely, and the skills aspect includes the value of being wise and fair, the use of techniques that are in accordance with the natural style. individuals and taking various actions are carried out in the right way. Meanwhile, several aspects of mainstream competency include aspects of knowledge, skills and personality.